Characteristics of Ionospheric Scintillation over Hong Kong from 2019 to 2024 Based onS4c - Haili Lin; Hao Liu; Dongsheng Zhao; Kefei Zhang; Suqin Wu; Craig M. Hancock (Advances in Space Research, 2026)

A difference-characteristics-based de-spiking approach for ADV velocity data under unsteady flow conditions - Yue Chen; Ping Gong; Wenjun Yang; Haili Lin (Ocean Engineering, 2026)

Boosting pH-universal hydrogen evolution of the In/Cu3P Mott-Schottky heterojunction electrocatalyst by constructing the ohmic contact and promoting water activation - Pengfei Du; Fang Li; Huiqin Yu; Jing Cao; Yuan Ma; Haili Lin (Fuel, 2026)

Development of an “Off-On” Fluorescence Sensing System Based on Nitrogen-Doped Carbon Quantum Dot/Fe³⁺ for Sensitive Detection of Cysteine - Lihao Jiang; Wenjie Dong; Yongjian Pan; Jianyuan Lin; Shancai Guo; Teng Wang; Fuhang Xu; Haili Wang; Chunjie Bai; Lihua Teng; Jianghua Chen (Journal of Fluorescence, 2026)

Driving mechanisms of distinct seasonal phytoplankton dynamics in a low-latitude basin revealed by multi-platform observations - Weinan Li; Edward A. Laws; Luping Song; Yichong Wang; Zengchao Xu; Chao Xu; Yibin Huang; Feipeng Xu; Lizhen Lin; Wupeng Xiao; Xin Liu; Haili Wang; et al. (Marine Environmental Research, 2026)

Adsorption-diffusion of trace organics in Baijiu on porous Fe2O3 - Qianxi Jiang; Manjiao Chen; Xinjun Hu; Weiqiang Zhou; Fan Zhao; Liangliang Xie; Haili Yang; Jinlong Yu; Zhoujun Lin; Caihong Shen (Journal of Food Engineering, 2026)

Unraveling the Tectonic Evolution of the Eastern Jiangnan Orogen, South China: Constraints From Basalts of Trace Elements, Nd Isotope, and Geochronology - Jiandong Sun; Xuehui Zhang; Jinsong Lv; Haili Li; Shiru Lin (Island Arc, 2026)
The Jiangnan Orogen has long been recognized as an ideal location for Precambrian geologists to study Neoproterozoic tectonic movements. However, the paleogeographic location of the South China Craton within the Rodinia supercontinent and the associated geodynamic mechanisms remain contentious. This research presents results from Laser Ablation Inductively Coupled Plasma Mass Spectrometry (LA‐ICP‐MS) zircon U–Pb dating, whole‐rock geochemistry, and Nd isotopes of early Neoproterozoic Jinshan basalts from the Zhangcun Formation. The basalts, dated at approximately 844 Ma, display a tholeiitic affinity, characterized by high MgO (8.19–13.70 wt.%), moderate TiO 2 (0.89–1.40 wt.%), and positive ε Nd ( t ) values (+ 1.35 to +3.53). Normalized rare earth element (REE) patterns and primitive mantle‐normalized trace element distributions indicate a slight enrichment of light rare earth elements (LREE) and a significant enrichment of large ionic lithosphere elements (LILEs), comparable to E2 basalts from the East Scotia Ridge back‐arc basin. It is suggested that the Jinshan basalts originated from a slightly depleted asthenospheric mantle, combined with recycled slab melt. When integrated with existing regional data, these basalts from the eastern Jiangnan Orogen exhibit notable geochemical anomalies, including elevated LREE and incompatible element ratios, as well as lower ε Nd ( t ) values, in contrast to back‐arc basin basalts from the central Jiangnan Orogen. This study proposes that the observed geochemical disparities between the eastern and central Jiangnan Orogen are attributed to varying degrees of slab rollback within the Yangtze Block during the early Neoproterozoic. Furthermore, evidence from prolonged arc magmatism and extensional tectonics related to slab rollback supports the conclusion that the South China Craton is positioned at the periphery of the Rodinia supercontinent.

Effect of calcium chelation on the physio-chemical characteristics and rehydration behavior of spray-dried casein-rich powder - Qiantong Zhong; Shucan Luo; John Fizpatrick; Langye Jiang; Zonglin Guo; Jie Lin; Hua Zheng; Haili Zeng; Canhu Wu; Songbai Zheng; Yan Gu; Christelle Turchiuli; et al. (Journal of Food Engineering, 2025)

Mechanisms of toxic metal(loid) migration in the slag-soil-groundwater continuum: Geochemical evidence from an abandoned industrial complex - Peng Zhao; Haili Zhang; Xuefeng Yang; Haiyan Wang; Muhammad Adnan; Yunlong Wu; Yuhui Liu; Lin Guo; Hai-Bo Qin; Baohua Xiao; Shengguo Xue (Journal of Cleaner Production, 2025)

Sankey diagram mapping of greenhouse gas emissions in road infrastructure projects: A cradle-to-laid perspective - Yaning Qiao; Lin Zhu; Haili Cao; Zhijun Liu; Gaoxin Wang; Fanran Meng (Sustainable Cities and Society, 2025)

Genetic identification and characterization of quantitative trait loci for wheat grain size-related traits independent of grain number per spike - Tao Li; Yanyan Tang; ZhengXi Lin; Jinghui Wang; Juanyu Zhang; Qiang Li; Furong Huang; Junjun Liang; Haili Zhang; Zehou Liu; Jun Li; Wuyun Yang; et al. (Theoretical and Applied Genetics, 2025)

Exploring the gelation potentials of chicken heart batter: From by-product to product - Mingxia Li; Langye Jiang; Zonglin Guo; Jie Lin; Hua Zheng; Wencheng Lin; Haili Zeng; Jiankun Wu; Hongtao Lei; Shaozong Wu (Food Chemistry, 2025)

Advancements in Hybrid and Combined Biological Technologies for Treating Polluted Gases: A Comprehensive Review - Haili Gong; Yonglin Liu; Tingzheng Yang; Lin Liu; Xuechen Li; Chuantao Gu; Zhenyu Jin; Debao Li; Weiliang Wang (Water, Air, & Soil Pollution, 2025)

Application of data-driven mixing parameterization scheme in a regional ocean model - Qingfeng Feng; Guoqing Han; Yu Liu; Xiayan Lin; Bo Li; Xiaoqian Gao; Changming Dong; Yinghui He; Haili Wang (Ocean Modelling, 2024)

A clean process for liquid-phase synthesis of α-PbO based on the selective leaching of lead sulfate from spent lead paste - Zhangqing Chen; Kui Huang; Guoliang Huang; Xinke Shan; Lin Wei; Haili Dong; Jujun Ruan (Journal of Environmental Chemical Engineering, 2024)

Major contributions of agricultural management practices to topsoil organic carbon distribution and accumulation in croplands of East China over three decades - Yue Pu; Lin Yang; Lei Zhang; Haili Huang; Ganlin Zhang; Chenghu Zhou (Agriculture, Ecosystems & Environment, 2024)

From disinfectants to antibiotics: Enhanced biosafety of quaternary ammonium compounds by chemical modification - Yuhan Mai; Zhiyou Wang; Yang Zhou; Guodong Wang; Jingyi Chen; Yuxin Lin; Panpan Ji; Wei Zhang; Qian Jing; Liyun Chen; Zheng Chen; Haili Lin; et al. (Journal of Hazardous Materials, 2023)

A chromosome-level genome assembly reveals that tandem-duplicated CYP706V oxidase genes control oridonin biosynthesis in the shoot apex of Isodon rubescens - Yuwei Sun; Jie Shao; Haili Liu; Hua Wang; Guangyi Wang; Jianhua Li; Yaping Mao; Zhuo Chen; Ke Ma; Lin Xu; Yong Wang (Molecular Plant, 2023)

Quantifying the direct effects of long-term dynamic land use intensity on vegetation change and its interacted effects with economic development and climate change in jiangsu, China - Feixue Shen; Lin Yang; Lei Zhang; Mao Guo; Haili Huang; Chenghu Zhou (Journal of Environmental Management, 2023)

Identification of three wheat near isogenic lines originated from CB037 on tissue culture and transformation capacities - Huiyun Liu; Haili Ma; Wei Zhang; Wanqing Wang; Jiajie Wu; Ke Wang; Zhishan Lin; Xingguo Ye (Plant Cell, Tissue and Organ Culture (PCTOC), 2023)

Higher pH is associated with enhanced co‐occurrence network complexity, stability and nutrient cycling functions in the rice rhizosphere microbiome - Yaping Guo; Bin Song; Anqi Li; Qi Wu; Haili Huang; Na Li; Ying Yang; Jonathan Miles Adams; Lin Yang (Environmental Microbiology, 2022)
The rice rhizosphere microbiota is crucial for crop yields and nutrient use efficiency. However, little is known about how co‐occurrence patterns, keystone taxa and functional gene assemblages relate to soil pH in the rice rhizosphere soils. Using shotgun metagenome analysis, the rice rhizosphere microbiome was investigated across 28 rice fields in east‐central China. At higher pH sites, the taxonomic co‐occurrence network of rhizosphere soils was more complex and compact, as defined by higher average degree, graph density and complexity. Network stability was greatest at medium pH (6.5

Determination of groundwater sustainable yield using a numerical modelling approach for the Table Mountain Group sandstone aquifer, Rawsonville, South Africa - Lixiang Lin; Haili Lin (Hydrogeology Journal, 2019)

A typical groundwater storage assessment in the Tugela area, South Africa - Haili Lin; Lixiang Lin (Hydrogeology Journal, 2019)

Excess iron alters the fatty acid composition of chloroplast membrane and decreases the photosynthesis rate: a study in hydroponic pea seedlings - Shijian Xu; Dongmei Lin; Haili Sun; Xiaoming Yang; Xinfang Zhang (Acta Physiologiae Plantarum, 2015)

Numerical modeling and environmental isotope methods in integrated mine-water management: a case study from the Witwatersrand basin, South Africa - Haile Mengistu; Abera Tessema; Tamiru Abiye; Molla Demlie; Haili Lin (Hydrogeology Journal, 2015)

Clinical Value of ELISA-MPT64 for the Diagnosis of Tuberculous Pleurisy - Zhonghua Liu; Changtai Zhu; Hua Yang; Haili Hu; Yonghong Feng; Lianhua Qin; Zhenling Cui; Aixiao Bi; Ruijuan Zheng; Ruiliang Jin; Lin Fan; Zhongyi Hu (Current Microbiology, 2012)

Impact of BTG2 expression on proliferation and invasion of gastric cancer cells in vitro - Lin Zhang; Haili Huang; Kai Wu; Mengwei Wang; Benyan Wu (Molecular Biology Reports, 2010)

Reduced MTA1 Expression by RNAi Inhibits in Vitro Invasion and Migration of Esophageal Squamous Cell Carcinoma Cell Line - Haili Qian; Ning Lu; Liyan Xue; Xiao Liang; Xueyan Zhang; Ming Fu; Yongqiang Xie; Qimin Zhan; Zhihua Liu; Chen Lin (Clinical & Experimental Metastasis, 2005)